Effects of aid for trade on extensive and intensive margins of greenfield FDI - Ly-My, Dung (2022)
Using a panel dataset of 105 developing countries for the period 2003–15, this paper assesses the effects of Aid for Trade (AfT) on greenfield FDI flows to the aid-recipient countries. Particularly, this paper classifies the total dollar value of greenfield FDI flows to each recipient country in terms of four different layers: the extensive and intensive margins of projects as well as the extensive and intensive margins of source countries. Applying the system GMM estimator, this paper finds that AfT not only increases the dollar value of FDI flows to the recipient countries but also helps diversify the greenfield projects and source countries. In addition, this paper finds that AfT has a greater effect for greenfield FDI from donor (developed) countries than from non-donor (developing) countries. Among the three components of AfT, aid for trade-related infrastructure and aid for trade policy regulations are found to have positive links with greenfield FDI, irrespective of source-country groups, yet their effects are larger for developed source countries. In contrast, aid for building productive capacity hinders greenfield FDI flows from non-donor countries, while it promotes greenfield FDI from donor countries. We offer some explanations for this finding.